2021
DOI: 10.3389/fpsyg.2021.781304
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Cognitive Differences in Semantic Processing Between Native Speakers and Proficient Learners of Mandarin Chinese

Abstract: The present study aimed to investigate the neural mechanism underlying semantic processing in Mandarin Chinese adult learners, focusing on the learners who were Indo-European language speakers with advanced levels of proficiency in Mandarin Chinese. We used functional magnetic resonance imaging technique and a semantic judgment task to test 24 Mandarin Chinese adult learners (L2 group) and 26 Mandarin Chinese adult native speakers (L1 group) as a control group. In the task, participants were asked to indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The only exceptions are that Chinese students typically spend more time on learning maths (Stevenson et al, 1986) and that Chinese characters are used in maths textbooks along with Arabic digits. The Chinese language uses complex characters that are different from alphabetic languages and that might potentially lead to increased visuo-spatial ability (Lai et al, 2021;Likhanov et al, 2018;Nelson et al, 2009;Rodic et al, 2015, but see Likhanov et al, 2023); and vice versa: language abilities development (and mathematics achievement) are positively linked with spatial visualization and orthographic awareness (Yang et al, 2021;Yang & Meng, 2020). Verbal and spatial ability will be controlled in the current study.…”
Section: Current Studymentioning
confidence: 99%
“…The only exceptions are that Chinese students typically spend more time on learning maths (Stevenson et al, 1986) and that Chinese characters are used in maths textbooks along with Arabic digits. The Chinese language uses complex characters that are different from alphabetic languages and that might potentially lead to increased visuo-spatial ability (Lai et al, 2021;Likhanov et al, 2018;Nelson et al, 2009;Rodic et al, 2015, but see Likhanov et al, 2023); and vice versa: language abilities development (and mathematics achievement) are positively linked with spatial visualization and orthographic awareness (Yang et al, 2021;Yang & Meng, 2020). Verbal and spatial ability will be controlled in the current study.…”
Section: Current Studymentioning
confidence: 99%
“…Further, several neuroimaging studies have shown that learning Chinese as L2 in adults may lead to increased activation of brain regions involved in visuo-spatial analysis (e.g. bilateral occipital and fusiform areas) for processing orthographical information of Chinese characters 29 , 30 . This in turn may enhance spatial skill processing more broadly.…”
Section: Introductionmentioning
confidence: 99%